Pengaruh Keluarga (TKI) terhadap Perilaku Disiplin Belajar Siswa SD di Kabupaten Tulungagung - Hidayati, Anis; Zuhdi, Muh. Sholihuddin (Efektor, 2019)
The purpose of this study was to determine whether there is a significant influence between family variables on the behavior of elementary school students in the discipline of learning Junjung Village, Sumbergempol District, Tulungagung. This research is a quantitative approach using the associative type of research. Methods of data collection in the form of a questionnaire, observation, documentation, and interview. The population were all students of grade V and VI in the Junjung Village of 201 students. The samples were 34 students of grade V and VI that one or both parents work as migrant workers abroad a number. The sampling technique using purposive sampling. The data analysis technique used is a simple linear regression and effective contribution previously done of normality test, linearity, and classical assumption. Based on the results of a simple linear regression analysis output, data showed Sig 0,000. So, the ratio is 0,000 < 0,05, which means it can be concluded that there is influence between family variables to the discipline learned primary school students in the Junjung Village, Sumbergempol District, Tulungagung. Behavior learning discipline students with parents who work as migrant workers abroad were low due to the functioning of the family are also low.